2010
DOI: 10.1002/int.20407
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and discrete event optimization for automated decisions for in-queue flights

Abstract: The paper discusses simulation and optimization of in-queue flights, analyzed as discrete-event systems. Simulation is performed in a platform, based on MATLAB program functions and SIMULINK dynamic models. Regime optimization aims to maximize the controllability of the queue and minimize the fuel consumption of each aircraft (AC). Because of mutual preferential independence, a hierarchical additive value function is constructed, consisting of fuzzily estimated parameter value functions and weight coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Many real-life problems such as games (Jordan et al, 2010;Amato and Shani, 2010), robotics (Spaan and Melo, 2008), traffic light control (Mohammadian, 2006;Le and Cai, 2010) or air traffic (Sislak et al, 2008;Dimitrakiev et al, 2010), occur in dynamic environments. Agents that interact in this kind of environment need techniques to help them, e.g., to reach some goal, to solve a problem or to improve performance.…”
Section: Background and Notationmentioning
confidence: 99%
“…Many real-life problems such as games (Jordan et al, 2010;Amato and Shani, 2010), robotics (Spaan and Melo, 2008), traffic light control (Mohammadian, 2006;Le and Cai, 2010) or air traffic (Sislak et al, 2008;Dimitrakiev et al, 2010), occur in dynamic environments. Agents that interact in this kind of environment need techniques to help them, e.g., to reach some goal, to solve a problem or to improve performance.…”
Section: Background and Notationmentioning
confidence: 99%
“…Under a crisis, their solution is to dismiss employees and wait for more favourable conditions [1]. Most managers believe that preventing crises by planning specific actions in the event of an adverse event is costly and the benefits are not always proven [2][3][4][5]. Some studies have found that managers do not invest resources in crisis prevention because they believe that the crisis will, in most cases, unfold differently than their expectations [6,7].…”
Section: Introductionmentioning
confidence: 99%